Seeking Arabs but looking at Indonesians: Snouck Hurgronje’s Arab lens on the Dutch East Indies - Fogg, K (Taylor and Francis, 2018)
Christiaan Snouck Hurgronje (1857-1936) was at his core an Arabist, rather than a scholar of Southeast Asia or even Islam in the Dutch East Indies. An Arab lens is evident in his early work on the Hijaz and in his later scholarship for the Dutch colonial government. Snouck Hurgronje’s work The Acehnese, in particular, evidenced a thoroughly comparative approach, verging at times on a focus outside of Southeast Asia, and throughout a preference for Arab orthodoxy. He found Indonesians to be inferior Muslims, and he saw their indigenous cultural practices as non-Islamic. It is important to remember Snouck Hurgronje’s Arab lens when considering his work and his legacy.